2021
DOI: 10.1155/2021/6797786
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Content on Methane Desorption Characteristics in Coal and Its Effect on Outburst Prediction

Abstract: Coal and gas outburst is a dynamic phenomenon with violent eruptions of coal and gas from the working coal seam. It has been proved that rapid desorption within a short period is necessary for the occurrence of an outburst. Due to the limitation of the present test condition, gas desorption characterization in coal with different moisture content for the first several seconds (0–60 s) has not been researched sufficiently. In this study, initial desorption characterization of gas in coal with different moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…17−19 It is a general belief that when the initial velocity of gas release tends to be higher, the coal seam is to more likely to have outburst. 36 Figure 4 indicates that Δp falls with the growth of water content, and its rate declines and to be flat. This indicates that moisture has an prohibitive impact on the emission of gas.…”
Section: Results Of Adsorption Constant (A)mentioning
confidence: 98%
See 1 more Smart Citation
“…17−19 It is a general belief that when the initial velocity of gas release tends to be higher, the coal seam is to more likely to have outburst. 36 Figure 4 indicates that Δp falls with the growth of water content, and its rate declines and to be flat. This indicates that moisture has an prohibitive impact on the emission of gas.…”
Section: Results Of Adsorption Constant (A)mentioning
confidence: 98%
“…The rate and capacity of gas release in coal seams can be used to examine the emission and transfer of coal seam gas, and play a predictive role in gas outburst. It is a general belief that when the initial velocity of gas release tends to be higher, the coal seam is to more likely to have outburst Figure indicates that Δ p falls with the growth of water content, and its rate declines and to be flat.…”
Section: Results and Analysismentioning
confidence: 99%
“…17 From the free surface to the inside, it is pressure unloading zone, stress concentration zone, and original rock stress zone in order, and the risk of coal outburst within the pressure relief zone has been eliminated. [18][19][20][21] Zhang et al 22 studied the coal pillar failure mechanism; the results indicated that the coal pillar can be divided into broken zone, stable zone, and collapsed zone, in which the stabilized zone accounts for one-third of the coal pillar width and plays a decisive role in coal pillar failure. Shi et al 23 investigated the movement law, the failure mechanism and the fracture evolution law of goaf-side entry driving in thick coal seams through experiments and numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Mining pressure theory shows that, under the influence of mining operation, the roof stress will be redistributed 17 . From the free surface to the inside, it is pressure unloading zone, stress concentration zone, and original rock stress zone in order, and the risk of coal outburst within the pressure relief zone has been eliminated 18–21 . Zhang et al 22 studied the coal pillar failure mechanism; the results indicated that the coal pillar can be divided into broken zone, stable zone, and collapsed zone, in which the stabilized zone accounts for one‐third of the coal pillar width and plays a decisive role in coal pillar failure.…”
Section: Introductionmentioning
confidence: 99%